2014
DOI: 10.7567/jjap.53.06jg02
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 nanowire arrays through hydrothermal growth method and their pH sensing characteristics

Abstract: The use of a TiO2 nanowire (NW) hydrothermally grown on an fluorine-doped tin oxide (FTO) substrate as a separated sensing electrode of an extended-gate field-effect-transistor (SE-EGFET) pH sensor is demonstrated. Sensing responses to the prepared samples in a wide pH range (2–12) are presented and compared with responses of a film-type TiO2 electrode. The pH sensors with the NW-type and film-type electrodes show a sensitivity of 62 and 50 mV/pH, respectively, and a comparably good linearity in the pH range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, several reports revealed super Nernstian values can be achieved. The highest values from the reported articles were 62.87 mV/pH for PdO [ 23 ], 61.44 and 62.0 mV/pH for TiO 2 [ 22 , 41 ], and 71.4 mV/pH for Pd-PdO [ 42 ]. Moreover, it was reported that a mixture of vanadium with 5% tungsten oxide achieved a sensitivity value of 68 mV/pH [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, several reports revealed super Nernstian values can be achieved. The highest values from the reported articles were 62.87 mV/pH for PdO [ 23 ], 61.44 and 62.0 mV/pH for TiO 2 [ 22 , 41 ], and 71.4 mV/pH for Pd-PdO [ 42 ]. Moreover, it was reported that a mixture of vanadium with 5% tungsten oxide achieved a sensitivity value of 68 mV/pH [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 The utilization of such advanced nanostructure on dye-sensitized solar 20 cells, 2 quantum-dot solar cells, 3 photoelectrochemical water splitting, 4 gas sensor 5 and batteries 6 boost the development of nanostructural materials. nanowires, nanotube or nanoporous structure) has gained intense attention due to their unique chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…(a) SEM and (b) High-resolution TEM image and XPS spectra of (c) Ti 2p and (d) O1s for the TiO 2 nanowire grown with 0.22 ml TiCl 4 added 5. Photoluminescence emission spectra of TiO 2 nanowires with different lengths were measured with excitation wavelength of 337 nm at room temperature.…”
mentioning
confidence: 99%
“…Due to high chemical stability, the TiO 2 based films are considered good for pH sensitive layers and a few studies concerning TiO 2 as a pH sensing layer have been reported as well [16][17]. The major studies concerning TiO 2 based pH sensors include their use in ion sensitive field effect transistor (ISFET) and extended gate field effect transistor (EGFET) [18,19]. However, in such realizations the sensors exhibited low sensitivity due to the intrinsic properties of TiO 2 films.…”
mentioning
confidence: 99%
“…Another disadvantage was that the reported sensors also required a reference electrode to operate. For these reasons, the pH sensors using metallic ion (Ru) doped TiO 2 or surface modification of the material by using TiO 2 nanotubes (NTs) or nanowires (NWs) were also proposed [17,19]. The nanostructured surface array significantly increases the electrode surface area, which increases the number of adsorption sites for H 3 O + ions and hence increases the pH sensitivity [17].…”
mentioning
confidence: 99%